THE INTRA-INDUSTRY SPILLOVERS OF INDONESIAN RIGHT OFFERINGS - Abdur Rafik; Embun Arafah (MIX: JURNAL ILMIAH MANAJEMEN, 2019)
This study aims to examine the spillover effect of right offerings to the industry on the Indonesian Stock Exchange in the period 2009-2016. This study is designed using event study methodology. In total, there are 96 issuing companies (issuers) and 1205 non-issuing companies (non-issuers) used as the sample which was obtained using a purposive sampling technique. The test for information content on the right issues was conducted using standard t-test on the average cumulative abnormal return of issuers and non-issuers in the period t-10 to t+10 around the issuance. The research found positive abnormal returns for issuers in t0 to t+4 but did not confirm the spillover effect to non-issuers over the observed (window) periods. The average cumulative abnormal returns are randomly distributed during the window period. These results confirm the absence of intraindustry effect of right issues on the non-issuers’ performance